PPP1R12B inhibits cell proliferation by inducing G0/G1 phase arrest via PAK2/β-catenin axis in hepatocellular carcinoma - Zhang, Yangqianwen; Liu, Shuowu; Bai, Mixue; Zhao, Zihan; Wang, Shan; Bao, Meiyu; Bao, Jinxia; Shen, Siyun; Lu, Shuang; Xiong, Ying; Gu, Gaoxiang; Wang, Hongyang; et al. (Frontiers in Cell and Developmental Biology, 2025)
Protein phosphatase 1 regulatory subunit 12B (PPP1R12B) is a regulatory subunit of protein phosphatase 1. While our previous study identified the inhibitory role of PPP1R12B in hepatocellular carcinoma (HCC), the precise molecular mechanisms underlying its anti-proliferative effects remain unclear. Herein, we demonstrated that PPP1R12B expression is significantly downregulated in HCC tissues and serves as an independent prognostic marker for favorable patient outcomes. Additionally, overexpression and silence of PPP1R12B experiments showed that PPP1R12B overexpression restricted cell proliferation and colony formation in vitro, and inhibited xenografted tumor growth in vivo, while its knockdown had opposite effects. Mechanistically, PPP1R12B could interact with p21-activated kinase 2 (PAK2) to suppress β-catenin expression and phosphorylation at Ser675, thereby impeding its nuclear translocation and subsequent transcriptional activation of Cyclin D1. This cascade culminated in G0/G1 phase cell cycle arrest. Furthermore, analysis of TCGA-HCC datasets confirmed inverse correlations between PPP1R12B and PAK2 or CTNNB1 (β-catenin) expression. Collectively, our findings elucidated a novel tumor-suppressive role of PPP1R12B in HCC through modulation of the PAK2/β-catenin/Cyclin D1 axis.